Performance of laboratory tests used to measure blood phenylalanine for the monitoring of patients with phenylketonuria. Issue 2 (2nd October 2019) - Moat, Stuart J.; Schulenburg‐Brand, Danja; Lemonde, Hugh; Bonham, James R.; Weykamp, Cas W.; Mei, Joanne V.; Shortland, Graham S.; Carling, Rachel S.
Abstract: Analysis of blood phenylalanine is central to the monitoring of patients with phenylketonuria (PKU) and age‐related phenylalanine target treatment‐ranges (0‐12 years; 120‐360 μmol/L, and >12 years; 120‐600 μmol/L) are recommended in order to prevent adverse neurological outcomes. These target treatment‐ranges are based upon plasma phenylalanine concentrations. However, patients are routinely monitored using dried bloodspot (DBS) specimens due to the convenience of collection. Significant differences exist between phenylalanine concentrations in plasma and DBS, with phenylalanine concentrations in DBS specimens analyzed by flow‐injection analysis tandem mass spectrometry reported to be 18% to 28% lower than paired plasma concentrations analyzed using ion‐exchange chromatography. DBS specimens with phenylalanine concentrations of 360 and 600 μmol/L, at the critical upper‐target treatment‐range thresholds would be plasma equivalents of 461 and 768 μmol/L, respectively, when a reported difference of 28% is taken into account. Furthermore, analytical test imprecision and bias in conjunction with pre‐analytical factors such as volume and quality of blood applied to filter paper collection devices to produce DBS specimens affect the final test results. Reporting of inaccurate patient results when comparing DBS results to target treatment‐ranges based on plasma concentrations, together with inter‐laboratory imprecision could have a significant impact on patient management resulting in inappropriate dietary change and potentially adverse patient outcomes. This review is intended to provide perspective on the issues related to the measurement of phenylalanine in blood specimens and to provide direction for the future needs of PKU patients to ensure reliable monitoring of metabolic control using the target treatment‐ranges.